Analisis Faktor Pengendali Konflik Keagenan Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Amelinda, Rita (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2018)
The purpose of this research is to measure the influence between agency conflict’s factors to the value of the firm with dividend policy as the moderating variable. Some of variables which are used in this research such as Free Cash Flow Ratio, Leverage, Return on Asset, GCG’s Implementation (CGPI), Dividend Policy, danValue of The Firm (Tobin’s Q). This research sample consisted of 126 observations which are the listed company in Indonesia Stock Exchange (IDX) during 2008-2014 period and they also are the company with the best GCG index. The results showed thatFree Cash Flow Ratio, Leverage, Return on Asset, GCG’s Implementation (CGPI), Dividend Policy have significant effect simultaneously on Value of The Firm (Tobin’s Q). While in partial, only GCG’s Implementation (CGPI) which doesn’t has significant effect onValue of The Firm (Tobin’s Q). On the other hand, dividend policy significantly moderated the influence of the other 4 independent variables to the value of the firm.